Avaliação dos aspectos clínicos e laboratoriais no diagnóstico de pacientes com suspeita de dengue em Fortaleza-Ceará, 2010 - Gomes, Almira Maria Monteiro (2012)
Dengue is transmitted by blood-sucking mosquitoes of the species of the genus Aedes aegypti and albopictus. Dengue virus (DENV) belongs to the genus Flavivirus of the Flaviviridae family and has four serotypes that were designated as: DENV-1, DENV-2, DENV-3 and DENV-4. The disease can manifest as an acute infectious disease characterized by a wide clinical spectrum ranging from asymptomatic forms of infection or undifferentiated fever to severe forms, with bleeding and / or shock. This study had as objective to describe the epidemiological, clinical and laboratory features of patients with suspected dengue fever treated at the St Joseph Hospital of Infectious Diseases (HSJ) and the Hospital Nossa Senhora da Conceição (HDNSC) in the period from February to December 2010. Thus, we recruited 93 patients, 86 met the inclusion criteria. Patients were recruited by an active search in emergencies and in the ward of these hospitals and underwent a follow-up protocol through an initial clinical evaluation form (from day 1 to day 5 of illness) and an evaluation form following (from the 6° to 7° day of illness). Were performed at least two measurements of hematocrit, platelets, and biochemical tests and specific tests for dengue. The signs and symptoms more prevalent in patients with suspected dengue were fever, headache and myalgia. Twenty-five patients (29%) had spontaneous bleeding manifestations and the cutaneous bleeding (petechiae and ecchymosis) were the most frequent (15%). When evaluating the female population of reproductive age, 6% had metrorrhagia. The tourniquet test was performed in 80 patients and was positive in 20 patients. Of 86 patients, 48 (55,8%) were positive for dengue at least one of the techniques: immunochromatography NS1 (16%), RT-PCR (19%), IgM ELISA (44%), IgM immunochromatography (42%) and NS1 ELISA (27%). The dengue virus was detected in 16 patient and, DENV-1 in 1 patient (6.2%), DENV-2 in 14 patients (87.5%) and DENV-3 in 1 patient (6.2%). Twenty- six patients (54,1%) met the criteria of the Ministry of Health (MOH) Classic Dengue (DC), 10 (20,8%) of Dengue Hemorrhagic Fever (DHF) and 12 (25%) of Dengue with complication (DCC). The relationship bet ween females and males were approximately 1.1/1, with higher prevalence in young adults The criterion for severity of MOH, 60% of suspected dengue cases were classified as grade II and none as grade IV. Plasma extravasation of criteria recommended by MOH, hypoalbuminemia was present in 5 patients (10,4%). The drop in hematocrit higher than 20% after hydration was observed in only 4 patients (8,3%). During the study period, two patients were diagnosed with dengue and leptospirosis, and one patient complicated with idiopathic thrombocytopenic purpura, these patients had a benign outcome. Therefore we stress the need for early diagnosis, before the development of severe manifestations, of policies to eradicate Aedes and structure a reference service.